If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 1overx = 6 Reorder the terms: 1eorvx + x = 6 Solving 1eorvx + x = 6 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-1x' to each side of the equation. 1eorvx + x + -1x = 6 + -1x Combine like terms: x + -1x = 0 1eorvx + 0 = 6 + -1x 1eorvx = 6 + -1x Divide each side by '1orvx'. e = 6o-1r-1v-1x-1 + -1o-1r-1v-1 Simplifying e = 6o-1r-1v-1x-1 + -1o-1r-1v-1 Reorder the terms: e = -1o-1r-1v-1 + 6o-1r-1v-1x-1
| 14x(x-y)+(x-y)=0 | | 6x-2(-6x+7)=130 | | 2(x^2-476)=0 | | 42=-7x | | 510=-10(-8x+5) | | ln(x)=ln(8)-2ln(x) | | 10-49=39 | | 4p-6=18 | | 4x+2(3x+4)=128 | | 5(x+2)-3(x-2)=2x+4 | | -38=-4x+5(4x+18) | | P(7)+P(8)+P(9)+P(10)+P(11)+P(12)+P(13)+P(14)= | | 2h+12=8h-36 | | 5(-6x+13)=275 | | 34-35= | | -9(-6x+8)=468 | | P(2)+P(3)+P(4)+P(5)+P(6)+P(7)+P(8)+P(9)= | | -2x-6(-x-10)=16 | | 3(x-0.8)=(4x+4) | | cos(2x)+3cosx+2=0 | | 5(2-x)+5=10-4x | | cos*2x+3cos*x+2=0 | | 18+2x+0.666x=4 | | 2x+3(4x-14)=112 | | 6x+3x+7.3=5+35.2 | | 4y+x=5(2x-y) | | 6x+4(-4x-14)=-176 | | 5m^2-50m=0 | | 4x+3(-3x+13)=89 | | 7+(-5)=12 | | 0=0.3*4180*(t-20)+0.1*385*(t-400) | | x-3x+5=3x-0.5 |